Branding of destinations - Árni Friðberg Helgason 1982-; Svavar Sigurðarson 1986- (2012)
Differentiation between Iceland and Norway can be hard for international tourists with limited knowledge of the Nordic countries. The primary objective of this research is to obtain a better understanding on what it is that international tourists perceive as differential factors between Iceland and Norway as destinations. To do so, a research question was laid out asking how destinations with natural and other common characteristics, can work to differentiate themselves through promotional imagery. A theoretical framework discussing theory related to destination branding and destination image is presented to provide a foundation for the research of this thesis. The thesis reports results from a structured questionnaire survey, which aimed to analyze if tourist could distinguish between Iceland and Norway by looking at images from both countries. Results from the survey indicate that tourists are only able to distinguish between the two countries to a certain extent. Results also indicate that people from countries that are closer to Iceland and Norway have a stronger image and more knowledge about the two countries.